The Role of Neutrophil-to-Lymphocyte Ratio (NLR) as a Predictor of Lymph Node Metastasis in Papillary Thyroid Carcinoma Patients in Cipto Mangunkusumo Hospital - Yulian, Erwin Danil; Andrian, Christopher Rico (http://dharmais.co.id/, 2025)
Background: Pre-treatment inflammatory parameters based on blood tests can serve as prognostic predictors in cancer, one of which is an elevated neutrophil-to-lymphocyte ratio (NLR). However, the role of NLR as a predictor of lymph node metastasis (LNM) in papillary thyroid carcinoma (PTC) remains controversial. This study was conducted to evaluate the role of NLR as a predictor of LNM in patients with PTC.Method: This cross-sectional analytical study was conducted at RSUPN Dr. Cipto Mangunkusumo from March to September 2024. The research utilized secondary data from the medical records of PTC patients. The receiver operating characteristic (ROC) curve was employed to determine the NLR cut-off value. Bivariate analysis was performed using the Chi-Square test, and multivariate analysis was conducted using multiple logistic regression. A p-value of 0.05 was considered statistically significant.Results: A total of 75 subjects were included in the study. ROC analysis showed an area under the curve (AUC) of 0.656. An NLR cut-off value of 2.34 yielded significant results (p = 0.03; OR = 3.15; 95% CI: 1.22–8.14) with sensitivity and specificity of 64%. Tumor size (p = 0.019), extrathyroidal extension (p 0.001), and papillary thyroid carcinoma variants (p = 0.002) were significantly associated with LNM. Patients with tumor sizes 4 cm had a lower risk of LNM (OR 0.28; 95% CI: 0.11–0.75). After adjusting for confounding variables, multivariate analysis revealed that subjects with high NLR had a 6.17-fold increased risk of LNM (aOR = 6.17; 95% CI: 1.68–22.64). Conclusion: Preoperative NLR in PTC patients is significantly associated with LNM. Tumor size, extrathyroidal extension, and aggressive variants of papillary thyroid carcinoma are significantly associated with LNM and influence the relationship between NLR and LNM.